The Effects of Government Loans on Youth Empowerment: A Case Study of Youth Livelihood Program, Jinja - Elisha Gome (Uganda Christian University, 2023)
This research was contacted on a topic entitled “The Effects of Government Loans on Youth Empowerment, A case study of Youth Livelihood Program, Jinja District”. It was carryout an assessment on the government loans if they helped to empower the youth. For example, like acquiring the knowledge and skills from the different projects that were operating such as poultry keeping, brick laying, piggery rearing, hair dressing, carpentry and many others. These were some of the research findings when I went to collect data from the area of the study which was Jinja District. The study involved three (3) of its objectives that is; to establish the effect of training and sensitization on promotion of youth empowerment in Jinja District, to establish the effect of stakeholder mobilization on the promotion of youth empowerment in Jinja District, to establish the challenges facing youth entrepreneurs while accessing government loans in Jinja District and the details were presented in the descriptive statistics shown by the frequency and percentage and the level of agreement represented in the tables. The majority of the respondents were in the age bracket of between 18-25 years and 26-34 years. 60 years and above represented the least of the respondents. The age group represented by 25.0%, 43.8% and 2.5% respectively. It can therefore be concluded that the majority of the respondents were in the most productive age brackets of their life, with young brains ready to run livelihood programs that can change their standards of living and are reasonably able to learn new skills and knowledge for a better living. The research findings also revealed that 62.5% of the respondents were males and 37.5% were female. This indicated that there is no balance of both women and men who get involved in the youth livelihood programs of Jinja district since even the youth leaders, focal point persons and DCDO were all men. However, since men continue to dominate as seen by the high number of men engaged in youth livelihood programs compared to women, this calls for further sensitization of women youths to encourage them join youth livelihood programs so as to change their standards of living. The findings represent the views of the two sex groups about the “effects of government loans on youth empowerment with a case study of youth livelihood programs in Jinja district.” This was necessary for the study to get a balanced picture of the respondents’ views
This is a dissertation.